Work-life conflict and intention to leave among teachers: The role of working time arrangements - Nogues, Sarah; Tremblay, Diane-Gabrielle (American Journal of Social Sciences and Humanities, 2025)
Attrition is a salient issue in the teaching profession, which also observes important work-life conflict. This paper assesses the influence of working time arrangements on teacher work-life conflict and intention to leave. Our descriptive results indicate that teachers experience high levels of work-family conflict and indicate moderate intention to leave. We ran ordinal logistic regressions to assess the impact of various working time arrangements onto teacher work-family conflict and intention to leave. After adjusting for sociodemographic variables, effective use of flexible hours was associated with lesser odds of experiencing conflict, while unavailability of reduced working time and study leaves was associated with greater odds of experiencing conflict. Access to, and effective use of personal/family leaves was associated with less intention to leave. However, not being able to reduce one’s work hours or to access a study leave was associated with increased intention to leave. Overall, our results point to a need for more control over the amount of hours they work, to attend to non-work needs. Our findings shed light on the reasons behind teacher attrition with regards to work-life conflict. These findings reinforce the necessity for a greater access to leaves, voluntary reduced working time and flexible hours for teachers. Investing in these key resources may reduce teacher work-life conflict and intention to leave, and thus contribute to teacher retention in the profession.